Histological and lectin histochemical studies on the olfactory mucosae of the Korean roe deer, Capreolus pygargus. Issue 2 (April 2015) - Park, Changnam; Ahn, Meejung; Kim, Jeongtae; Kim, Seungjoon; Moon, Changjong; Shin, Taekyun
Highlights: The olfactory mucosae of roe deer consist of the olfactory epithelium and the lamina propria containing Bowman's glands. The olfactory epithelium consists of galectin-3-positive supporting cells, protein gene product 9.5 (PGP 9.5)-positive receptor cells and basal cells. Carbohydrate terminals, including N-acetylglucosamine, fucose and N-acetylgalactosamine groups, were identified in olfactory epithelia and Bowman's glands using lectin histochemistry. Abstract: The morphological features of the olfactory mucosae of Korean roe deer, Capreolus pygargus, were histologically studied using the ethmoid turbinates containing the olfactory mucosae from six roe deer (male, 2–3 years old). The ethmoid turbinates were embedded in paraffin, and histochemically evaluated in terms of the mucosal characteristics. Lectin histochemistry was performed to investigate the carbohydrate-binding specificity on the olfactory mucosa. Lectins, including Triticum vulgaris wheat germ agglutinin (WGA), Ulex europaeus agglutinin I (UEA-I), and soybean agglutinin (SBA) were used for the N-acetylglucosamine, fucose and N-acetylgalactosamine carbohydrate groups, respectively. Histologically, the olfactory mucosa, positioned mainly in the caudal roof of the nasal cavity, consisted of the olfactory epithelium and the lamina propria. The olfactory epithelium consisted of protein gene product (PGP) 9.5-positive olfactory receptor cells, galectin-3-positive supporting cells and basal cells. Bowman's glands in the lamina propria were stained by both the periodic acid Schiff reagent and alcian blue (pH 2.5). Two types of lectin, WGA and SBA, were labeled in free border, receptor cells, supporting cells and Bowman's glands, with the exception of basal cells, while UEA-I was labeled in free border, supporting cells and Bowman's glands, but not in receptor cells and basal cells, suggesting that carbohydrate terminals on the olfactory mucosae of roe deer vary depending on cell type. This is the first morphological study of the olfactory mucosa of the Korean roe deer to evaluate carbohydrate terminals in the olfactory mucosae.